Molecular Epidemiology of Multi-Drug Resistant Acinetobacter baumannii Isolated in Shandong, China - Jiang, Meijie; Liu, Lijuan; Ma, Yunhua; Zhang, Zhijun; Li, Ning; Zhang, Fusen; Zhao, Shuping (Frontiers in Microbiology, 2016)
Acinetobacter baumannii is an emerging nosocomial pathogen prevalent in hospitals worldwide. In order to understand the molecular epidemiology of multi-drug resistant (MDR) A. baumannii, we investigated the genotypes of A. baumannii isolated from ten hospitals in Shandong, China, from August 2013 to December 2013, by pulsed field gel electrophoresis (PFGE) and multilocus sequence typing (MLST). Antimicrobial resistance genes were analyzed by PCR and DNA sequencing. By PFGE analysis, we discovered 11 PFGE types in these ten hospitals. By MLST, we assigned these isolates to 12 sequence types (STs), 10 of which belong to the cloning complex CC92, including the prevalent ST369, ST208, ST195, and ST368. Two new STs, namely ST794 and ST809, were detected only in one hospital. All isolates of the MDR A. baumannii were resistant to carbapenem, except 2 isolates, which did not express the blaOXA-23 carbapenemase gene, indicating blaOXA-23 is the major player for carbapenem resistance. We also discovered armA is likely to be responsible for amikacin resistance, and may play a role in gentamicin and tobramycin resistance. aac(3)-I is another gene responsible for gentamicin and tobramycin resistance. In summary, we discovered that the majority of the isolates in Shandong, China, were the STs belonging to the CC92. Besides, two new STs were detected in one hospital. These new STs should be further investigated for prevention of outbreaks caused by A. baumannii.